2010
DOI: 10.1089/ten.tea.2009.0508
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Matrix Metalloprotease-2 Levels by Mechanical Loading of Three-Dimensional Mesenchymal Stem Cell Constructs: Impact onIn VitroTube Formation

Abstract: Angiogenesis is essential to tissue reconstitution, is sensitive to mechanical stresses, and currently represents one of the major challenges in tissue engineering. The pro-angiogenic matrix metalloprotease-2 (MMP-2) is upregulated in mechanically loaded mesenchymal stem cells (MSCs). Therefore, MMP-2 may provide a regulating link between angiogenesis and the surrounding mechanical conditions. This study aimed to modulate MMP-2 levels by mechanical loading of MSCs embedded in a three-dimensional matrix as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…Similarly, the ability of a higher concentration of GM6001 to block CM-induced capillary network formation as compared to the control media suggests that MMP-2 present in the CM plays an important role in CM-induced angiogenesis. The role of MMP-2 in inducing endothelial network formation reported in this study is supported by Glaeser et al who had reported that pro-MMP-2 secreted by MSCs is further activated by endothelial cells and the total MMP-2 plays a pivotal role in endothelial network formation [74].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the ability of a higher concentration of GM6001 to block CM-induced capillary network formation as compared to the control media suggests that MMP-2 present in the CM plays an important role in CM-induced angiogenesis. The role of MMP-2 in inducing endothelial network formation reported in this study is supported by Glaeser et al who had reported that pro-MMP-2 secreted by MSCs is further activated by endothelial cells and the total MMP-2 plays a pivotal role in endothelial network formation [74].…”
Section: Discussionsupporting
confidence: 82%
“…MMPs that are expressed by MSCs can contribute to that role during the interaction of MSCs and ECs [4]. Glaeser and colleagues [59] demonstrated that the inhibition of MMP-2 attenuated the tube-like formation. Under mechanical stimulation by MSCs, the secretion of proMMP-2 and the activity of MMP-2 were induced and, as a result, this induction contributes to angiogenesis stimulation.…”
Section: Mscs Express Mmps and Timps To Regulate Different Processesmentioning
confidence: 99%
“…1, 2 This specific regeneration potential arises not only from the MSC ability to differentiate into various mesenchymal cell types to replace cells in damaged tissues but also from paracrine effects of the cells modulating injury or immune responses. 3, 4, 5, 6 However, healing capacity of mesenchymal tissues, especially of bone and muscle, has been shown to decline with increasing age. 7, 8, 9 In particular, our previous in vivo study showed an age-related delay in the course of bone healing, resulting in an altered microstructure and in reduced mechanical properties of the regenerated tissue.…”
mentioning
confidence: 99%